2015
DOI: 10.1615/critrevimmunol.2015012327
|View full text |Cite
|
Sign up to set email alerts
|

The Ezrin-Radixin-Moesin Family of Proteins in the Regulation of B-Cell Immune Response

Abstract: Dynamic reorganization of the cortical cytoskeleton is essential for numerous cellular processes including B and T cell activation and migration. The Ezrin, Radixin and Moesin (ERM) family proteins play structural and regulatory roles in the rearrangement of plasma membrane flexibility and protrusions through their reversible interaction with cortical actin filaments and plasma membrane. Recent studies demonstrate that ERM proteins are not only involved in cytoskeletal organization but also offer a platform fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 101 publications
(122 reference statements)
4
57
0
Order By: Relevance
“…The ERM family proteins are in this context of particular interest as they orchestrate the assembly and stabilization of plasma membrane interactions through their ability to interact with transmembrane proteins and the cytoskeleton (Fehon, McClatchey et al 2010). In doing so, they provide structural links to strengthen the cell cortex and facilitate several key cellular process, including the membrane dynamics, substrate adhesion, cell survival, determination of cell shape, polarity, formation of membrane protrusions, cell adhesion and motility (Pore andGupta 2015, Pines, Levi et al 2017). In this study, we demonstrated that induction of moesin expression is a robust and early event in the cuprizone model.…”
Section: Discussionmentioning
confidence: 99%
“…The ERM family proteins are in this context of particular interest as they orchestrate the assembly and stabilization of plasma membrane interactions through their ability to interact with transmembrane proteins and the cytoskeleton (Fehon, McClatchey et al 2010). In doing so, they provide structural links to strengthen the cell cortex and facilitate several key cellular process, including the membrane dynamics, substrate adhesion, cell survival, determination of cell shape, polarity, formation of membrane protrusions, cell adhesion and motility (Pore andGupta 2015, Pines, Levi et al 2017). In this study, we demonstrated that induction of moesin expression is a robust and early event in the cuprizone model.…”
Section: Discussionmentioning
confidence: 99%
“…Ezrin is the prototypic member of the ezrin protein subfamily, which serves as a linker between the plasma membrane and the cytoskeleton. Indeed, these proteins act as intracellular scaffolds , regulating B‐ and T‐cell activation . A recent study showed that ezrin plays a role in regulating inflammation, via limiting the B‐cell IL‐10 production .…”
Section: Discussionmentioning
confidence: 99%
“…The results of in vitro studies have shown that chemotaxis and T-cell receptor (TCR)/B-cell receptor (BCR) signaling induce rapid dephosphorylation of ERM proteins (through a decrease in phosphatidylinositol 4,5-bisphosphate levels or through phosphatases) and thus cytoskeletal relaxation and cell polarization. 4,12 After TCR or BCR stimulation, ERM proteins are then rephosphorylated by kinases (eg, Rhoassociated protein kinase, protein kinase Cu, and lymphocyteorientated kinase) [13][14][15][16] and relocate to the distal pole complex. 17 MSN and ezrin are involved in formation of the immunologic synapse (IS) through participation in microclustering of the antigen receptor complex and recruitment or exclusion of specific proteins.…”
mentioning
confidence: 99%